2015
DOI: 10.1093/nar/gkv614
|View full text |Cite
|
Sign up to set email alerts
|

ECHO-liveFISH:in vivoRNA labeling reveals dynamic regulation of nuclear RNA foci in living tissues

Abstract: Elucidating the dynamic organization of nuclear RNA foci is important for understanding and manipulating these functional sites of gene expression in both physiological and pathological states. However, such studies have been difficult to establish in vivo as a result of the absence of suitable RNA imaging methods. Here, we describe a high-resolution fluorescence RNA imaging method, ECHO-liveFISH, to label endogenous nuclear RNA in living mice and chicks. Upon in vivo electroporation, exciton-controlled sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…Similar localization of Cy3 emission was observed when a conventional FISH protocol involving washing procedures was used (Figure S5). The emission observed using probe YR2–2_28S coincided with the previous studies employing 28S rRNA-specific probes;[12,23,24] therefore, we concluded that the self-quenching probe detects target RNA in cells.…”
Section: Resultssupporting
confidence: 89%
“…Similar localization of Cy3 emission was observed when a conventional FISH protocol involving washing procedures was used (Figure S5). The emission observed using probe YR2–2_28S coincided with the previous studies employing 28S rRNA-specific probes;[12,23,24] therefore, we concluded that the self-quenching probe detects target RNA in cells.…”
Section: Resultssupporting
confidence: 89%
“…S2B). To have information about the spatial localization of ribosomes, we labeled the 28s ribosomal RNA of the ribosomes by using exciton-controlled hybridization-sensitive fluorescent oligonucleotide (ECHO) probes (33). In the absence of magnetic localization of the mRNA-NPs, we observed a strong background noise and a few natural hotspots (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…Time‐resolved imaging showed that fluorescence was much more intense at the mitotic phase than at the interphase, implying that relatively large quantities of mRNA are expressed as the cell divides. Later studies have shown the capability of ECHO probes to detect other intracellular RNA targets, including 28S rRNA and U3 small nucleolar RNA …”
Section: Hybridization‐based Probesmentioning
confidence: 99%